Analysis of Student Reversible Thinking Skills on Graph Concept - Sutiarso, Sugeng (Universitas Islam Negeri Raden Intan Lampung, 2020)
The ability of reversible thinking in mathematics has less attention, but most of the mathematical subject is reversible. This type of research was qualitative descriptive which aimed to analyze student’s reversible thinking skills on the graph concept. The subject of research were students of mathematics education, Faculty of Teacher Training and Education, Lampung University taking the graph theory in the academic year 2019/2020. Research subjects were 40 people selected by the total sampling technique. The research data was collected through tests, namely the question of Ramsey number. Data were analyzed descriptively with 3 stages, namely data reduction, data display, and conclusion. The results showed that 42.5% of students had reversible thinking skills and 57.5% of students did not have them. Based on the results of this study, it was concluded that most students did not have reversible thinking skills on graph concepts.